The Philosophy of Logical Atomism and Other Essays 1914-19 - Russell, Bertrand 1872-1970; Slater, John G. (London Allen & Unwin, 1986)
Taken from a series of influential lectures delivered by Russell during the second decade of the twentieth century, this is a brilliant introduction to logical atomism and its application to ontology and epistemology.
Keywords: 20th Century (1901-2000); Philosophy